G479(P) Use of the rehabilitation complexity scale to assess dependency and rehabilitation complex in patients receiving in-patient neurorehabilitation at a region neuroscience centre (rnsc). (May 2019) - Smallbone, T; Hameed, B; Reyes Peyeras, C; Eve, M; Fernandez, D; Wright, I; Sharples, PM
Abstract : Aim: To investigate feasibility of using the Rehabilitation Complexity Scale (RCS) to assess rehabilitation needs in children receiving in-patient neurorehabilitation in a RNSC. Background: The RCS is established in adult neurorehabilitation practice for assessing complexity of care and therapy needs in hospital and community settings. Few data exist concerning its use in paediatric neurorehabilitation. Methods: Children receiving specialist in-patient neurorehabilitation were scored on the RCS-Extended (RCS-E) by the multi-disciplinary team at weekly neurorehabilitation clinical meetings over 15 months. Patients' functional status was scored simultaneously by King's Outcome Score for Childhood Head Injury (KOSCHI) and Modified Rankin Scale (MRS). Demographic details were obtained from the clinical neurorehabilitation database. Statistical analyses were performed using IBM SPSS Statistics Version 21. Results: 180 RCS-E, KOSCHI and MRS assessments were obtained in 34 patients, mean age=7.6 years (range 0.1–17). 43% were male, 57% female. 78% had ABI. There were significant differences between RCS-E, scored on neurorehabilitation admission and hospital discharge, for total RCS-E (admission: mean=12.97, SD=2.48; discharge: mean=9.50, SD=3.70; paired t test, p<0.001) and for care (p<0.001) and therapy subscales (p<0.001). No correlations were found between age and admission or discharge total RCS-Es (both, p>0.05). Admission total RCS-E did not predict neurorehabilitation duration (r=0.26, p=0.10), but there was a relationship between rehabilitation duration and discharge total RCS-E (r=0.40. p=0.005). In ABI patients, correlations were seen between admission and discharge total RCS-Es and contemporaneous KOSCHI (admission, r=−0.60, p<0.001; discharge, r=−0.75, p<0.001) and MRS (admission, r=0.76, p<0.001; discharge r=0.74, p<0.001) scores. Total RCS-E on neurorehabilitation admission did not predict discharge functional status, assessed by KOSCHI (r=0.12, p=0.55) or MRS (r=0.09; p=0.65). Applying adult RCS-E categories, 46% in-patient weeks were classed as high/very high dependency; 52% medium dependency and 2% low dependency. Trajectories of care and therapy needs could be identified. Conclusion: The RCS-E is easy to use in in-patient paediatric rehabilitation practice, despite issues around the applicability of definitions of care need. The measure is sensitive to change over time and correlates with functional status. Evidence that>50% total weeks of in-patient neurorehabilitation were classed as medium-level dependency supports provision of an outreach neurorehabilitation service.